Attitude Control of Linear System by Using Feed- Forward Constant-Amplitude Inputs - Parman, Setyamartana (2008)
Attitude control of a linear system equipped by constant amplitude inputs are studied. The inputs to be given to the system are feed-forward inputs, and the input shaping method is used to form time optimal inputs in small residual oscillation of its attitude angles. As a study, attitude maneuvers of a flexible satellite are studied. The satellite consists of a rigid main body and two flexible solar panels. In the modeling, the finite element method is used to discret the flexible displacement of solar panels. Under constantamplitude control inputs, results indicate that the maneuver induces an undesirable motion of the satellite as well as vibration of the solar panels. Then, time-optimal shaped inputs are applied to maneuver the satellite. By using shaped inputs, those reduce vibrations at large-amplitude natural frequencies, the expected pointing precision of the satellite can be satisfied.